Programa de fomento à educação integral no ensino médio: análise da implantação na rede estadual do município de Santarém-PA - SOUSA, Eli Conceição de Vasconcelos Tapajós (Universidade Federal do Oeste do Pará, 2021)
The purpose of this study is to analyze the implementation of the Program for the Promotion of Integral Education as a public policy of full secondary education (EMI) in the context of the secondary education reform, based on Law 13.415 / 2017, in the state public network in the municipality of Santarém -PA. For the development of the research, we use as method the qualitative approach. The methodological procedures adopted were a bibliographical review and documentary analysis, the first of which was based on theoretical sources such as Arreteche (1995), Araújo (2018), Cardozo (2009), Ciavatta and Ramos (2012), Colares e Ferreira (2015), Frigotto and Ciavatta (2003), Gomes and Colares (2017), Guará (2006), Gadotti (2009), Hofling (2001), Jacomeli (2011), Moll (2017), Romanelli (2010), Severino ; the second had as sources Provisional Measure 746/2016, the Ordinance of Higher Education in the Ministry of Education No. 727, June 13, 2017, which establishes new guidelines, new parameters and criteria for the Program for the Promotion of Teaching Schools EMTI, in accordance with Law 13.415, of February 16, 2017, LDB 9.394 / 96, the State Education Plan, the Pedagogical Political Project of the schools surveyed and the Minutes of implementation of the program in the state network . This work deals with Brazilian educational policy as part of a public policy of social regulation in the context of the economic, political and social transformations that shaped the model of national production, according to the demands of the capitalist mode of production, deals with integral education as public policy educational program based on the Law of Reform of Secondary Education 13.415 / 2017, with the Program for the Promotion of Implantation of Integral Secondary Education, its implementation in the current political, economic and educational scenario in Brazilian society and, finally, situates the state of Pará and the municipality of Santarém in the context of integral education, as well as the implementation of the Program for the Promotion of Integral Education in the context of the reform of secondary education in the schools surveyed. It was concluded that there is a lack of understanding of the program, since the public policies implemented require permanent study and monitoring by all those involved in the implementation process and that the proposal for the state education network does not address the needs and aspirations of schools and students.